1997
DOI: 10.1055/s-2007-979077
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of High Altitude Trekking on Body Composition and Resting Metabolic Rate

Abstract: Resting metabolic rate (RMR) and body composition were evaluated in 12 healthy volunteers before and after 16 days of high altitude trekking and climbing. RMR was measured by indirect calorimetry and body composition by electrical impedance. A 29% reduction in energy intake during high altitude exposure was observed. Fat mass loss averaged about 2.2 kg (p < 0.05) and lean body mass about 1.1 kg, which was almost significant (p = 0.07). As expected, estimated RMR at the end of the expedition--calculated by pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 8 publications
7
34
0
1
Order By: Relevance
“…In this study, body weight, Lee's index, fat mass, and the fat mass to body weight ratio in the H group rats were all significantly lower than those in the N group, which was consistent with previous studies (Armellini et al, 1997;Netzer et al, 2008;Lippl et al, 2010). Armellini et al (1997) thought that the reduction in energy intake may contribute to weight loss in individuals undergoing high altitude training.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, body weight, Lee's index, fat mass, and the fat mass to body weight ratio in the H group rats were all significantly lower than those in the N group, which was consistent with previous studies (Armellini et al, 1997;Netzer et al, 2008;Lippl et al, 2010). Armellini et al (1997) thought that the reduction in energy intake may contribute to weight loss in individuals undergoing high altitude training.…”
Section: Discussionsupporting
confidence: 92%
“…Armellini et al (1997) thought that the reduction in energy intake may contribute to weight loss in individuals undergoing high altitude training. Lippl et al (2010) found that the body weight of obese men was significantly lower at a 2650 m altitude for 7 d, which may be due to a significantly higher resting metabolic rate and leptin level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting, that the authors also mention possible health benefits of longterm work in hypoxic conditions as some recent papers about hypoxia training indicate (e.g. Boyer and Blume, 1984;Rose et al, 1988;Kayser, 1992Kayser, , 1994Armellini et al, 1997;Schobersberger et al, 2003;Haufe et al, 2008;Netzer et al, 2008).…”
Section: Problems With Present Guidancementioning
confidence: 99%
“…The whole discussion is dominated by (fictive) risk assumptions, while some data suggest that intermittent hypoxia of moderate degree also has some benefit instead of risk for persons who are regular exposed as there are an amelioration of the lipid profile, insulin resistance, leptin, body weight, and others (e.g. Boyer and Blume, 1984;Azevedo 378 T. Küpper et al et al, 1995;Armellini et al, 1997;Grosfeld et al, 2002;Schobersberger et al, 2003;Simler et al, 2006;Yingzhong et al, 2006;Netzer et al, 2008). In conclusion, a more detailed specialized analysis of the individual exposure is necessary to provide adequate advice for health and safety.…”
Section: Problems With Present Guidancementioning
confidence: 99%